2020
DOI: 10.1091/mbc.e19-12-0707
|View full text |Cite
|
Sign up to set email alerts
|

Transition of podosomes into zipper-like structures in macrophage-derived multinucleated giant cells

Abstract: Macrophage fusion resulting in the formation of multinucleated giant cells (MGCs) is a multistage process that requires many adhesion-dependent steps and involves the rearrangement of the actin cytoskeleton. The diversity of actin-based structures and their role in macrophage fusion is poorly understood. In this study, we revealed hitherto unrecognized actin-based zipper-like structures (ZLSs) that arise between MGCs formed on the surface of implanted biomaterials. We established an in vitro model for the indu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 66 publications
(97 reference statements)
0
11
0
Order By: Relevance
“…Moreover, E-cadherin neutralizing antibodies impair IL-4 induced macrophage fusion, especially in early stages of differentiation ( Moreno et al, 2007 ), and fusion is diminished in macrophages derived from E-cadherin deficient mice ( Van de Bossche et al, 2009 ; Van de Bossche et al, 2012 ). Fusion-efficient macrophages are characterized by membrane extension, called podosomes, which form zipper-like structures at cell fusion sites ( Balabiyev et al, 2020 ). E-cadherin is probably implicated in the generation of these zipper-like structures as neutralizing antibodies disrupt formation of these structures and subsequent fusion ( Balabiyev et al, 2020 ).…”
Section: Formation Of Multinucleated Giant Cells Through Macrophage F...mentioning
confidence: 99%
“…Moreover, E-cadherin neutralizing antibodies impair IL-4 induced macrophage fusion, especially in early stages of differentiation ( Moreno et al, 2007 ), and fusion is diminished in macrophages derived from E-cadherin deficient mice ( Van de Bossche et al, 2009 ; Van de Bossche et al, 2012 ). Fusion-efficient macrophages are characterized by membrane extension, called podosomes, which form zipper-like structures at cell fusion sites ( Balabiyev et al, 2020 ). E-cadherin is probably implicated in the generation of these zipper-like structures as neutralizing antibodies disrupt formation of these structures and subsequent fusion ( Balabiyev et al, 2020 ).…”
Section: Formation Of Multinucleated Giant Cells Through Macrophage F...mentioning
confidence: 99%
“…It is induced in a STAT-6 dependent manner consequently to IL-4 or IL-13 treatments [ 44 , 105 , 132 , 133 ]. In IL-4 stimulated macrophages, E-cadherin forms complexes with catenins that accumulate at the sites of cell contact [ 133 , 134 ]. Different approaches using treatment with specific antibodies and E-cadherin-deficient macrophages show that this protein participates through homotypic interaction in IL-4-induced MGC formation [ 44 , 133 ].…”
Section: Molecular Actors Involved In Cell-to-cell Fusionmentioning
confidence: 99%
“…A recent and elegant study demonstrated the existence of zipper-like structures in FBGCs. Indeed, this study revealed zipper-like structures that arise between mouse MGCs induced by IL-4 stimulation in vitro and following biomaterial implantation in vivo [ 134 ]. Using live imaging and super-resolution microscopy, the group of Ugarova showed that podosomes are the precursors of these zipper-like structures.…”
Section: Role Of Podosomes and Zipper-like Structures In Myeloid Cell Fusionmentioning
confidence: 99%
See 2 more Smart Citations